Transformational Leadership in Islamic Education Institution Through Social Media Engagement - Asmendri Asmendri; Milya Sari; Deni Asrida; Lita Sari Muchlis; Vicky Rizki Febrian; Nur Azizah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Transformational leadership in Islamic value-based educational institutions, such as Rumah Tahfidz Qur'an (RTQ), faces challenges in integrating traditional practices with modern innovations to improve academic quality. This study explores the effectiveness of transformational leadership in RTQ Surau Lakuak, focusing on the strategic use of social media. Using a descriptive qualitative approach, the research involves in-depth interviews and document analysis, guided by Kouzes and Posner's (2017) Leadership Challenge framework, which includes five core dimensions: Model the Way, Inspire a Shared Vision, Challenge the Process, Enable Others to Act, and Encourage the Heart. The findings indicate that leaders at RTQ Surau Lakuak effectively utilize social media to articulate their vision, enhance transparency, and foster community engagement. Key initiatives, such as digital donation campaigns, symbolic recognition, and community empowerment programs, have strengthened collaboration and ensured the sustainability of Qur'anic education programs. These practices are grounded in Islamic principles like ta'awun (cooperation) and deliberation, providing an adaptable leadership model for contemporary Islamic education. The study highlights the potential of applying the Leadership Challenge framework to address digital-era challenges, offering a replicable and innovative strategy for Islamic educational institutions in diverse contexts.